2003
DOI: 10.1136/oem.60.7.497
|View full text |Cite
|
Sign up to set email alerts
|

Course of low back pain among nurses: a longitudinal study across eight years

Abstract: Aims: To describe the course of low back pain (LBP) among nurses across eight years. Methods: A longitudinal study was performed with a follow up at 1 and 8 years among nurses employed by a large university hospital in Switzerland. A modified version of the Nordic Questionnaire was distributed to obtain information about demographic data, occupational activities, and various aspects of LBP. A clinical examination and several functional tests were used to overcome the problems associated with subjective pain re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
111
3
9

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(136 citation statements)
references
References 25 publications
13
111
3
9
Order By: Relevance
“…Abandonment due to pain in neck and arms is possibly less common because those are less disqualifying (18) . Yet, some authors (4,19) raise the hypothesis that no association between MSD in low back and work time is due to better coping strategies for physical loads, developed by more experienced professionals.…”
Section: Variables Frequencymentioning
confidence: 99%
“…Abandonment due to pain in neck and arms is possibly less common because those are less disqualifying (18) . Yet, some authors (4,19) raise the hypothesis that no association between MSD in low back and work time is due to better coping strategies for physical loads, developed by more experienced professionals.…”
Section: Variables Frequencymentioning
confidence: 99%
“…There is a high prevalence of LBP among staff members working in hospitals [1]. Of all the health care workers, a higher prevalence of LBP is reported among nurses [2,3]. A study among nurses in Sudayr region revealed that 53.2 % of the nurses had worked related LBP and a positive correlation was seen between place of work and pain duration [4].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of LBP is significant, as most nurses will have a persistent pain throughout their lifetime, proven by Maul et.al. [18], which may contribute to early retirement (8).…”
Section: Discussionmentioning
confidence: 99%